Central Nervous System Germ Cell Tumors: A Review of the Literature. (August 2018) - Kong, Ziren; Wang, Yaning; Dai, Congxin; Yao, Yong; Ma, Wenbin; Wang, Yu
Central nervous system germ cell tumors are rare intracranial tumors that mainly occur in pediatrics with substantial variation in the incidence among different regions and genders. Histologically, central nervous system germ cell tumors can be divided into germinomas and nongerminomatous germ cell tumors. The molecular pathology of central nervous system germ cell tumors, particularly germinomas, is mainly based on the presence of isochromosome 12p, gain-of-function of the KIT gene, and a globally low DNA methylation profile. Diagnoses and differential diagnoses are conducted through imaging, tumor marker detection, surgical biopsy, and cerebrospinal fluid cytology. Germinomas are often treated via whole-ventricular radiotherapy or neoadjuvant chemotherapy combined with reduced-dose whole-ventricular radiotherapy, whereas nongerminomatous germ cell tumors are mainly treated with chemotherapy, surgical resection, and radiotherapy (individually or in combination), depending on tumor composition. Because the main population of patients is pediatric, extending overall survival and reducing treatment side effects should be the main goals of future studies.